Unraveling the viral dark matter through viral metagenomics - Santiago-Rodriguez, Tasha M.; Hollister, Emily B. (Frontiers in Immunology, 2022)
Viruses are part of the microbiome and have essential roles in immunology, evolution, biogeochemical cycles, health, and disease progression. Viruses influence a wide variety of systems and processes, and the continued discovery of novel viruses is anticipated to reveal new mechanisms influencing the biology of diverse environments. While the identity and roles of viruses continue to be discovered and understood through viral metagenomics, most of the sequences in virome datasets cannot be attributed to known viruses or may be only distantly related to species already described in public sequence databases, at best. Such viruses are known as the viral dark matter. Ongoing discoveries from viral dark matter have provided insights into novel viruses from a variety of environments, as well as their potential in immunological processes, virus evolution, health, disease, therapeutics, and surveillance. Increased understanding of viral dark matter will continue with a combination of cultivation, microscopy, sequencing, and bioinformatic efforts, which are discussed in the present review.